Pengaruh Investment Opportunity Set, Liquidity, dan Corporate Social Responsibility terhadap Cash Holding - Mikyal Farialmira; Nuramalia Hasanah; Aji Ahmadi Sasmi (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This research aims to test and analyze the effect of Investment Opportunity Set, Liquidity, and Corporate Social Responsibility on Cash Holding. This study uses purposive sampling to select samples, using secondary data sources derived from the company’s annual report and sustainability report on non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. The final number of samples obtained was 52 companies with a total observation of 156 data. The data analysis technique used is panel data regression analysis through data processing performed on EViews 12 software. The results of testing the hypothesis of this study indicate that corporate social responsibility has no effect on cash holding, while investment opportunity set and liquidity has affect on cash holding.